Research on Resource Allocation and Management of Mobile Edge Computing Network - Zhang, Rui; Shi, Wenyu (Informatica, 2020)
The popularity of mobile Internet makes the application of mobile terminals need more computing resources, and cloud computing enables mobile terminals to handle application tasks that need high computing resources under the premise of maintaining small specifications. However, it is difficult to obtain high-quality low latency services as the mobile Internet edge is far away from the cloud computing center; hence mobile edge computing (MEC) is proposed. This study introduced computing resource allocation methods based on power iteration and system utility, applied them to the mobile edge computing network, and carried out simulation experiments in MATLAB software. The experimental results showed that the network throughput and system utility under the two resource allocation methods increased and the average transfer rate decreased with the increase of users in the mobile edge network; under the same number of access users, the edge network based on the system utility allocation method had higher throughput, average transfer rate and system utility.